Does Human Resource Management Practices Moderate The Relationship Between Nepotism and Attitude? - Mahdani Ibrahim; Maulana Alimin; Banta Karollah (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
This study aims to examine the moderating effect of human resource management practice (HRMP) variables on the relationship between nepotism variables and attitude variables (job satisfaction, organisational citizenship behaviour (OCB) and organisational commitment).A research sample of 300 workers in the three largest hospitals in Aceh (Dr. Zainoel Abidin General Hospital, Meuraxa General Hospital and Harapan Bunda Hospital). Primary data were obtained by distributing questionnaires to participants in the three hospitals with 100 questionnaires each.Data were analysed using simple regression and moderated regression analysis.The results of our analysis found that HRMPs have a moderating effect on the relationship between nepotism and job satisfaction and nepotism and organisational commitment.The moderating effect of HRMPs was not found in the relationship between nepotism and OCB.